The role of UGT1A1 polymorphism in the management of colorectal cancer - Babadi, Elham; Roudini, Kamran; Aalipour, Kianmehr; Alese, Olatunji B. (Oncology Reviews, 2025)
Colorectal cancer is a leading cause of cancer related deaths among patients worldwide, necessitating the development of more effective and tolerable therapies. Topoisomerase I inhibitors such as Irinotecan are integral components of chemotherapy regimens used in the management of colorectal, as well as esophageal, gastric, biliary tract, pancreatic, neuroendocrine, small bowel and anal carcinomas. Efficacy and toxicity of these regimens are however impacted by metabolism via the UGT1A1 pathways. This literature review provides a comprehensive overview of UGT1A1 polymorphism in patients with colorectal cancer, including recent developments and the future landscape. Recent literature elucidating the roles of oncogenes and predictive biomarkers on anti-cancer drugs and UGT1A1 genotypes are described. The lack of consensus in the clinical management of patients with colorectal cancer were also explored in depth. A comprehensive search was performed in multiple databases (including PubMed, Embase, Web of Science, Scopus, Research gate, and Google Scholar) to identify relevant articles published up to January 2024. A total of 79 clinical studies were included in this review. The epidemiology and frequency of UGT1A1 genes polymorphisms by race, gender, ethnicity, geographic location and stage of the cancer were correlated with drug metabolism, toxicity, and survival outcomes. The tole of UGT1A1 as a prognostic and predictive biomarker, including existing challenges in clinical application were also discussed extensively.